MICROTSIRCOULYATOR VIOLATION AT VERTEBRO-BAZILYARNIY INSUFFICIENCY - Геник, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the patients have the resulted results of research of being of microtsircoulyator river-bed with vertebro-bazilyar insufficiency by the biomicroscope of boulbar conjunctiva. Complication of microtsircoulyator violations is exposed with growth of degree of weight of disease.